2020
DOI: 10.5430/ijhe.v9n5p181
|View full text |Cite
|
Sign up to set email alerts
|

Global Perceptions of Faculties on Virtual Programme Delivery and Assessment in Higher Education Institutions During the 2020 COVID-19 Pandemic

Abstract: Amidst the outbreak of COVID-19 worldwide, virtually all national governments declared a “lockdown” of all institutions in a bid to curtail its spread. This posed serious challenges to programme delivery and assessment in Higher Education Institutions (HEIs), with foreseeable long and short-term consequences. This study investigated the effectiveness of virtual programme delivery and assessment in Higher Education Institutions (HEIs) during the COVID-19 (Corona Virus) pandemic, from a global perspective. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Some researchers (e.g., Booth, 2019 ) have anticipated CALA as an inevitable and irreversible trend in L2 assessment, which indicates the future of this field due to its advantages, including the individualized test process and simplified test administration. On the other hand, the on-going spread of COVID-19 has further facilitated this trend after online learning and online assessment have been acknowledged as an effective means to normalize the delivery of teaching and learning in challenging situations caused by natural disasters (Sasere and Makhasane, 2020 ). Based on a review of approximately 300 studies spanning 2002–2018 that examined the mainstream assessment tools in computer-assisted language learning, Bahari ( 2020 ) pointed out that CALA is moving toward integrated language skills assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers (e.g., Booth, 2019 ) have anticipated CALA as an inevitable and irreversible trend in L2 assessment, which indicates the future of this field due to its advantages, including the individualized test process and simplified test administration. On the other hand, the on-going spread of COVID-19 has further facilitated this trend after online learning and online assessment have been acknowledged as an effective means to normalize the delivery of teaching and learning in challenging situations caused by natural disasters (Sasere and Makhasane, 2020 ). Based on a review of approximately 300 studies spanning 2002–2018 that examined the mainstream assessment tools in computer-assisted language learning, Bahari ( 2020 ) pointed out that CALA is moving toward integrated language skills assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In actuality, the rapid advance of computer technology and unexpected natural disasters that limit physical contact such as the COVID-19 pandemic have made computer-assisted L2 assessment (CALA) pervasive in L2 learning and teaching at various levels, particularly at the tertiary level (Zhang and Qin, 2018;Qin and Zhang, 2019;Sasere and Makhasane, 2020). As one form of CALA, the CAIST integrates multiple language skills (e.g., reading, listening and speaking) to replicate the authentic language use tasks for evaluating learners' ability to deal with daily language use activities.…”
Section: Introductionmentioning
confidence: 99%
“…Digital learning fits almost perfectly into the notion of modern learning: "The MOOCs revolution promises to open up school-level and higher education by providing accessible, flexible, affordable courses, using a range of platforms. <…> Open education brings opportunities for innovation and exploration of new learning models and practices" (Peters, 2017;Saser & Makhasane, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the same vein, García-Peñalvo et al ( 2020 ) suggested introduction, training, and support of teaching staff and students to work on different assessment tasks, in addition to changes in departmental policy. The importance of training was also echoed in Sasere and Makhasane’s ( 2020 ) study recommendations, in which they investigated HE virtual teaching delivery and assessment during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%